An analysis of the conditions, paths and mechanisms for the formation of social capital in private colleges and universities - Huang Weiyue (SHS Web of Conferences, 2022)
Social capital is an effective social resource in colleges and universities. It plays an important role in promoting the level of running a school, especially in private colleges and universities. This thesis explored the internal needs of private higher institutions for social financing and expounded the conditions, elements and mechanisms for the formation of social capital in private higher education institutions by analyzing its social fund resources, school size and features of management system. It was concluding that it would be better to take reasonable and effective measures from the president, board of directors, former students, parents, teacher-student relations, school-enterprise cooperation, brand construction, etc. Thus it is full of references for private colleges and universities to make social capital act an effective part in it for a long time.